Digital Transformation of MSME Finance: The Role of Digital Financial Literacy, Digital Lifestyle, and Saving Decisions in Digital Banks (SDB) for Business Resilience - Carolina Ety Widjayanti; Wiwiek Rabiatul Adawiyah; Sudarto Sudarto; Najmudin Najmudin; Rio Dhani Laksana (Journal The Winners, 2026)
This research addressed a gap in Micro, Small, and Medium Enterprises (MSMEs) finance research, which has predominantly focused on digital credit adoption while paying limited attention to saving decisions in digital banks and their implications for business resilience. The study aims to examine the role of digital financial literacy and digital lifestyle in shaping saving decisions in digital banks and to explore how these decisions contribute to strengthening MSME resilience. Data were collected from MSME owners and managers and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that digital financial literacy and digital lifestyle positively influence saving decisions in digital banks. Furthermore, saving decisions in digital banks play an important role in enhancing business resilience and serve as a mechanism through which digital financial literacy and digital lifestyle contribute to sustainable business operations. The research extends the digital finance literature by conceptualizing digital-bank savings as a digitally enabled cash-management practice that supports financial discipline, fund separation, cash-flow documentation, and liquidity management among MSMEs. This perspective highlights that digital financial services are not only relevant for accessing external financing but also for strengthening internal financial management capabilities. The practical implications suggest the need for MSME-oriented digital banking services, financial literacy programs, and behavioral interventions that encourage safe, documented, and disciplined saving practices to support long-term business resilience in an increasingly digital financial ecosystem.